Hypertonic Saline in the Treatment of Hemorrhagic Shock - Vahidi, Elnaz (Adv J Emerg Med, 2017)
CONTEXT: The present review discusses different studies about the treatment of hemorrhagic shock (HS) with hypertonic saline (HTS). EVIDENCE ACQUISITION: We have searched the title in the most popular databases containing recent meta-analysis or randomized clinical trials (RCTs). RESULTS: We introduce the hemodynamic effects and mechanisms of action of HTS in HS. Evidence in this field shows controversial results. There are some data supporting the potential benefits of HTS infusion in HS. The goal of research in this field is to identify the best therapy in HS with the least mortality. CONCLUSION: Our conclusion shows that although HTS can decrease inflammatory response during HS, it can attenuate hypercoagulability and cause complications. There are no data supporting less mortality while treatment with HTS versus other fluids in HS.